RESOURCE-CONSTRAINED INNOVATION MANAGEMENT IN MSMES: BALANCING EXPLORATION, EXPLOITATION, AND RISK - Adang Haryaman; Wawan Ichwanudin (Organisasi Kreatif Indonesia Emas, 2024)
This conceptual paper develops an integrative framework for resource-constrained innovation management in micro, small, and medium enterprises (MSMEs). Drawing on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial-ecosystem literature, the paper explains how exploration, exploitation, experimentation, resource discipline, governance, and organizational learning can be organized into practical managerial routines. No primary survey, interview, experimental, or statistical data are claimed. The analysis proposes a staged cycle of diagnosis, experimentation, evidence review, governance, and resource reconfiguration. It further identifies implications for owner-managers, support institutions, and future empirical research. The framework emphasizes that capability development should be proportionate to enterprise constraints and evaluated through decision quality, learning, resilience, and business outcomes rather than adoption indicators alone.